A Question of Timing: 10-year Retrospective Analysis on the Use of Antenatal Steroids for Imminent Preterm Birth - Matlac, Dieter; Jonassen, Sinje; Fortmann, Mats Ingmar; Rody, Achim; Bossung, Verena (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Objective Antenatal steroids improve the neonatal outcome if they are administered within a therapeutic window of seven days before preterm birth. The aim of this study was to evaluate the timing of antenatal steroids for imminent preterm birth at a single center in Germany.Material and Methods A 10-year retrospective analysis of 843 preterm births between 24/0 and 33/6 weeks was performed from January 2008 to December 2017 at a German university hospital. We evaluated the timing of antenatal steroids according to the indication for their application. Descriptive statistics and binomial regression were performed to analyze factors influencing the timing of antenatal steroid administration.Results Of 843 preterm births below 34 weeks included in our study, 752 pregnant women received antenatal steroids (89.2%). Only 301/843 women (35.7%) gave birth within the optimal window of 7 days after antenatal steroids. 91/843 women (10.8%) did not receive steroids. 130/843 women (15.4%) only received one dose, 76/843 (9.0%) gave birth within 8 to 14 days, and 245/843 (29.1%) more than 14 days later. In a binomial regression model, preterm premature rupture of membranes (OR 3.40, 95% CI 1.81 to 6.39, p<0.001), fetal growth restriction (OR 3.27, 95% CI 1.63 to 6.58, p=0.001), and preeclampsia (OR 2.83, 95% CI 1.37 to 5.83, p=0.005) were positively associated with optimal timing.Conclusion Two thirds of women with preterm birth before 34 weeks received antenatal steroids outside the optimal therapeutic window. Further research is needed to achieve an optimal effect of antenatal steroids on neonatal outcome and to reduce untimely as well as unnecessary interventions.
Keywords: preterm birth; betamethasone; antenatal care; prediction; antenatal steroids